Today with troika; which is ‘the natural order of things’? - Sá, André Correia de (2013)
Juliet, the main female figure of the Ordem Natural das Coisas, oscillates in two interpenetrated narrative movements: the extreme representation of a simulated existence and an ironic deployment of an author that sees the novel as a self-reflective puzzle. The cohesion between these two symbolic systems is given by setting the diegesis in a depressive universe, through a poetics of death and silence with unparalleled lyrical effects. In this essay we seek light in some of these cases, crossing them, in some way, with the state of siege experienced by portuguese society in 2013.